Financial Management helps Financial Ratio Analysis to Share Price in the Largest Cigarette Company in Indonesia: Financial Management helps Financial Ratio Analysis to Share Price in the Largest Cigarette Company in Indonesia - Marjohan, Masno; Supratikta, Hadi (Benefit: Jurnal Manajemen dan Bisnis, 2024)
The purpose of this research is to find out the role of financial management as a tool to analyze financial ratios to share prices, which consist of cash ratio, net profit margin, and earnings per share, and simultaneously and partly in share prices of listed tobacco companies, in the Indonesian Stock Exchange. Exchange 2013-2022. The research sample is financial statements for 10 years. The data analysis method is a quantitative analysis method with SPSS analytical tools in the form of multiple linear regression. Version 25. The analysis shows that at the same time, the independent variable has a significant effect on stock prices. In the case of the shareholders' ratio variables, the net profit margin ha does not affect the stock price, while the earnings per share (EPS) has a significant effect on the stock price. Recommendations for future research are recommended to increase variables and companies.